2020
DOI: 10.1002/jbmr.4293
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia Definitions as Predictors of Fracture Risk Independent of FRAX®, Falls, and BMD in the Osteoporotic Fractures in Men (MrOS) Study: A Meta-Analysis

Abstract: Dual-energy X-ray absorptiometry (DXA)-derived appendicular lean mass/height 2 (ALM/ht 2 ) is the most commonly used estimate of muscle mass in the assessment of sarcopenia, but its predictive value for fracture is substantially attenuated by femoral neck (fn) bone mineral density (BMD). We investigated predictive value of 11 sarcopenia definitions for incident fracture, independent of fnBMD, fracture risk assessment tool (FRAX ® ) probability, and prior falls, using an extension of Poisson regression in US, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…This should result in lower prevalence of sarcopenia, especially in men, that are separate from changes in operational definition. Consequently, most studies report that more individuals are classified as sarcopenic according to EWGSOP1 than according to EWGSOP2 with a difference around 2–6% (range − 2 to 20%) [ 8 , 9 , 11 14 , 16 20 , 34 , 35 ]. Most studies have also found limited agreement between EWGSOP1 and 2 [ 8 , 10 , 14 – 21 ], while others have found a fair to good agreement [ 9 , 11 – 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…This should result in lower prevalence of sarcopenia, especially in men, that are separate from changes in operational definition. Consequently, most studies report that more individuals are classified as sarcopenic according to EWGSOP1 than according to EWGSOP2 with a difference around 2–6% (range − 2 to 20%) [ 8 , 9 , 11 14 , 16 20 , 34 , 35 ]. Most studies have also found limited agreement between EWGSOP1 and 2 [ 8 , 10 , 14 – 21 ], while others have found a fair to good agreement [ 9 , 11 – 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sarcopenia is known to be a risk factor for femoral neck fracture because of the increased risk of falling [ 54 , 55 ] and the greater impact on the femur bone during a fall caused by the loss of cushioning provided by the gluteus maximus muscle [ 56 ]. Furthermore, HD patients with sarcopenia exhibit a higher risk of falling-induced fragility fractures [ 45 , 57 ]. Therefore, CKD should be regarded as a condition that increases the risk of femoral fracture due to the frequent occurrence of sarcopenia in affected individuals.…”
Section: Osteoporosis and Sarcopenia In Hd Patientsmentioning
confidence: 99%
“…Estimates that reached statistical significance are highlighted in bold. We identified one large cohort 19 including 10 411 men in three countries (United States, Sweden, and China) that reported results of totally 40 validity tests of different sarcopenia definitions on different types of fractures ( Table 2). Thereby, the SDOC definition showed the strongest association to all four types of fractures (overall fractures, major osteoporotic fractures, osteoporotic fractures, and hip fractures).…”
Section: Resultsmentioning
confidence: 99%